2023
DOI: 10.3390/f14081674
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Soil Texture-Related Thinning Effects on Soil Microbial and Enzymatic Properties in a Semi-Arid Pine Forest

Cristina Lull,
Ricardo Gil-Ortiz,
Inmaculada Bautista
et al.

Abstract: Thinning is a practice that reduces competition for available soil resources, thereby promoting vegetation growth and affecting soil, which is involved in important ecosystem processes. Soil quality is directly influenced by various aspects such as ground cover, regional climate, and local microclimate, which can further be modified by forest thinning. In this study, the effect of tree thinning and climate on microbiological and enzymatic soil properties was investigated in an Aleppo pine (Pinus halepensis M.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 108 publications
2
4
0
Order By: Relevance
“…Plant diversity and element cycling in forest ecosystems depend on the enzymatic activity of the soil. The present investigation is consistent with previous studies that highlight the significance of enzymes, including but not limited to catalase, dehydrogenase, polyphenol oxidase, urease, chitinase, acid-phosphatase, nitrogenase, and invertase, in influencing soil processes and promoting plant diversity ( Lladó et al, 2017 ; Bhaduri et al, 2022 ; Lull et al, 2023 ; Zuccarini et al, 2023 ). The current study showed close relationships between enzyme activities and nutrient availability in soil microbes.…”
Section: Discussionsupporting
confidence: 93%
“…Plant diversity and element cycling in forest ecosystems depend on the enzymatic activity of the soil. The present investigation is consistent with previous studies that highlight the significance of enzymes, including but not limited to catalase, dehydrogenase, polyphenol oxidase, urease, chitinase, acid-phosphatase, nitrogenase, and invertase, in influencing soil processes and promoting plant diversity ( Lladó et al, 2017 ; Bhaduri et al, 2022 ; Lull et al, 2023 ; Zuccarini et al, 2023 ). The current study showed close relationships between enzyme activities and nutrient availability in soil microbes.…”
Section: Discussionsupporting
confidence: 93%
“…These results support the importance of the quality of organic matter in the microbial activity [78,79]. A high variability between sampling dates was observed indicating a high activity dependence with climate [44]. In fact, enzyme activity is extremely dependent on temperature, humidity, pH, substrate availability and other related soil chemical properties, as shown in several studies [80][81][82].…”
Section: Discussionsupporting
confidence: 85%
“…Soil carbon fractions are directly related to organic matter and microbial activity [63,64]. In a previous study, we found no direct improvement in SOC and WSOC content in a pine forest in the long term (eleven years after thinning) under a clay-loam soil texture by moderate thinning, but did under the same conditions under a low fertility sandy soil [44]. As explained above, the effects of thinning depend on multiple factors, and SOC and WSOC content can be improved or worsened depending on aspects such as the intensity of thinning, species, age, physicochemical properties of soils, microorganisms, etc.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations